THE INFLUENCE OF WORK DISCIPLINE, WORKS CULTURE AND INDIVIDUAL BEHAVIOR ON VILLAGE DEVICE PERFORMANCE - Siti Fatimah; Fredy Jayen; Abdul Kadir; Syamsiar Syamsiar (Value : Jurnal Manajemen dan Akuntansi, 2023)
This study aims at determining the effect of work discipline, work culture, and behavior partially on the performance of village officials in Kalumpang District, South Hulu Sungai Regency, and to determine the dominant variables. The method was multiple regression analysis to determine the variables that affect performance. The research was conducted on 35 village officials in the Kalumpang district, South Hulu Sungai Regency, and was carried out for 3 months. The results show that There is a partially significant effect between individual behavior on performance but there is no partial significant effect between work discipline and work culture on the performance of village officials, while the most dominant influencing variable is individual behavior.       Keywords: discipline, work culture, individual behavior and performance of village officials